Human Genetic Susceptibility to Native Valve Staphylococcus aureus Endocarditis in Patients With S. aureus Bacteremia: Genome-Wide Association Study - Moreau, Karen; Clemenceau, Alisson; Le Moing, Vincent; Messika-Zeitoun, David; Andersen, Paal S.; Bruun, Niels E.; Skov, Robert L.; Couzon, Florence; Bouchiat, Coralie; Erpelding, Marie L.; van Belkum, Alex; Bossé, Yohan; et al. (Frontiers in Microbiology, 2018)
Staphylococcus aureus infective endocarditis (SaIE) is a severe complication of S. aureus bacteremia (SAB) occurring in up to 22% of patients. Bacterial genetic factors and host conditions for SaIE have been intensely studied before; however, to date no study has focused on predisposing host genetic factors to SaIE. The present study aimed to identify genetic polymorphisms associated with SaIE by a Genome-Wide Association Study (GWAS) of 67 patients with definite native valve SaIE (cases) and 72 matched native valve patients with SAB but without IE (controls). All patients were enrolled in the VIRSTA cohort (Le Moing et al., PLOS ONE 2015) study. Four single nucleotide polymorphisms (SNPs) located on chromosome 3 were associated with SaIE (P < 1x10-5) without reaching conventional genome-wide significance. For all, the frequency of the minor allele was lower in cases than in controls, suggesting a protective effect of the minor allele against SaIE. The same association was observed using an independent Danish verification cohort of SAB with (n=57) and without (n=123) IE. Ex vivo analysis of aortic valve tissues revealed that SaIE-associated SNPs mentioned above were associated with significantly higher mRNA expression levels of SLC7A14, a predicted cationic amino acid transporter protein. Taken together, our results suggest an IE-protective effect of SNPs on chromosome 3 during the course of SAB. The effects of protective minor alleles may be mediated by increasing expression levels of SLC7A14 in valve tissues. We conclude that occurrence of SaIE may be the combination of a well-adapted bacterial genotype to a susceptible host.